Pembangunan Sumber Manusia Menurut Perspektif Islam - Basir, Siti Arni (Jurnal Usuluddin, 2004)
This article will discuss the importance of human resource development from Islamic perspective. The author also gives several examples of the human resource development programmes in Malaysia.